A comparative study on vulnerability and coping mechanisms between Rohingya refugee and Chakma IDP women - Rashid, Syeda Rozana; Forum on Women in Security and International Affairs (Bangladesh); Bangladesh Freedom Foundation (Dhaka : Forum on Women in Security and International Affairs : Bangladesh Freedom Foundation, 2005)
Comparative study with reference to refugee women belonging to Rohingya ethnic group of Burmese people, and internally dispaced women belonging to Chakma ethnic group of Asian people, living in Bangladesh.
"October 2005."
Includes bibliographical references.
Prefatory matter in Bengali.
Keywords: Women, Rohingya -- Bangladesh -- Social conditions; Women, Chakma -- Bangladesh -- Social conditions; Women refugees -- Bangladesh -- Social conditions; Internally displaced persons -- Bangladesh -- Social conditions